AB0469 Patient-Oriented Decision of Early Treatment of Rheumatoid Arthritis with Combination of Triple Conventional Disease Modifying Anti-Rheumatic Drugs or Tumor Necrosis Factor Inhibitors and Methotrexate (Prospective, Open-Label Clinical Trial). (10th June 2014) - Okada, M.; Matsuno, H.; Abe, C.; Katayama, K.; Kondo, M.; Sagawa, A.; Yamasaki, K.; Kishimoto, M.; Matsubara, T.
Abstract : Background: Early optimization of conventional disease modifying anti-rheumatic drugs (cDMARD) treatment is imperative as delay of biologics in certain patients potentially leads to irreversible functional disability. Bucillamine (BUC) is a unique cDMARD available in Japan in the past twenty years which was recently shown to augment the efficacy of methotrexate (MTX) and salazosulfapyridine (SASP) when they are administered together. Objectives: We examined the early institution of the triple combination therapy (TriD) before judging requirement of combination therapy of TNF inhibitors and methotrexate (TNFI) in daily practice setting. Methods: One hundred fourteen patients of early rheumatoid arthritis with worse prognosis based on the activity and known prognostic factors were incorporated in the study from 26 institutions belonging to Japan Association of Rheumatologists in Private practice (JARP). After careful informed consent, all patients by themselves decided to receive TriD therapy or TNFI therapy. Primary endpoint is average DAS28 score at 6 and 12 months, and secondary endpoint is clinical remission rate, functional remission rate and serum MMP-3 value at 3, 6 and 12 months, and modified Total Sharp Score at 12 months. Results: Fifty four patients and 30 patients completed 1 year treatment in TriD group and TNFI group, respectively, and both groups had significant improvement over the 12 months period. Mean DAS28 were comparable in TriD and TNFI groups at baseline 4.90±0.99 and 5.23±1.2 (p=0.13), 3.43±1.41 and 3.43±1.41 at 6 months, and 3.31±1.37 and 3.07±1.4 (p=0.39) at 12 months, respectively. The change between baseline and 12 months in the EULAR response rate and the CDAI were also similar in the two groups. There were no significant between group differences in the changes of modified Sharp score at 12 months as 4.2±6.6 in TriD and 3.8±8.4 in TNFI (p=0.86) at 12 months. Conclusions: With sufficient instruction and discussion between patients and physician, patients with active rheumatoid arthritis despite conventional DMARD therapy could choose either TriD or TNFI, appropriately. Patients-oriented decisions significantly reduced the cost of treatment without affecting the clinical and radiological outcome. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1939